Using 3D printing technology in prototype production to control the dimensions of complexly shaped products - Sproch, Filip; Schindlerova, Vladimira; Sajdlerova, Ivana (Manufacturing Technology Journal, 2020)
Prototype production is a key element in the process of developing a new product. The prototype is important both for the initial materialization of ideas and intentions for product design, as well as for subsequent assessment of the technological design of this design. 3D printing technology is also used today as a suitable technology for prototype production, especially for the possibility of relatively rapid adaptation to complex shape geometries, the ability to produce what would be difficult or impossible to produce with conventional technologies, and last but not least, the increasing availability of 3D printing equipment.This paper demonstrates the principle of production of auxiliary gauges, for checking the dimensions of a prototype product with complex shape, 3D printing and its further possible use in the conditions of an engineering company. The conclusions of the paper should show the possibility and suitability of integration of modern and classical production technologies in the conditions of piece or custom production.
Keywords: 3D Printing; Prototype Production; Auxiliary Gauges